2020
DOI: 10.3892/etm.2020.8998
|View full text |Cite
|
Sign up to set email alerts
|

Human umbilical cord MSC‑derived hepatocyte growth factor enhances autophagy in AOPP‑treated HK‑2 cells

Abstract: Mesenchymal stem cell (MSC) transplantation may serve as an important treatment modality in chronic kidney disease (CKD); however, the underlying mechanisms remain unclear. Advanced oxidation protein products (AOPP) have been demonstrated to induce renal tubular epithelial cell (RTEC) injury via autophagy inhibition. Therefore, the present study was performed to investigate the role of human umbilical cord-derived MSCs (hUC-MSCs) in RTEC autophagy. AOPP-treated HK-2 cells were co-cultured with hUC-MSCs or trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…The physiochemical characteristics of ARW enable it to easily penetrate the cell membrane, resulting in increased metabolism due to its antioxidative properties [42]. Furthermore, endogenous HGF expression in renal tubular cells has been reported in a few studies [11]. Correspondingly, this study strengthens the physiological role of HGF in PTEC, which warrants deeper investigation.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The physiochemical characteristics of ARW enable it to easily penetrate the cell membrane, resulting in increased metabolism due to its antioxidative properties [42]. Furthermore, endogenous HGF expression in renal tubular cells has been reported in a few studies [11]. Correspondingly, this study strengthens the physiological role of HGF in PTEC, which warrants deeper investigation.…”
Section: Discussionsupporting
confidence: 69%
“…Accumulating evidence has shown that MMPs are the main factors of extracellular matrix (ECM) degradation and that they activate multiple growth factors and cytokines linked with hypertrophy of kidneys, proliferation of tubular cells and fibrosis [9,10]. In addition, studies have shown that hepatocyte growth factor (HGF) and α-smooth muscle actin (α-SMA) play a central role in ECM accumulation in diabetic kidneys [11,12]. Therefore, protecting kidney cells by suppressing OS in DM may be a possible therapeutic approach for DN treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Feng et al 140 found that transplantation of sirtuin3-overexpression amniotic fluid stem cells serves as promoting therapeutic strategies for DN through activation of mitophagy and inhibition of apoptosis. Other studies confirmed that UCMSCs enhanced autophagy in advanced oxidation protein products–treated HK-2 cells through inactivation of the PI3K/Akt/mTOR pathway 141 , 142 . Intriguingly, upregulation of autophagy remarkably increased the secretion of TGF-β1 from MSCs and suppressed the proliferation of CD4 + T lymphocytes 143 , whereas inhibition of autophagy reduced the responsiveness of T cells to mitogen IL-2 and increased the production of immunosuppressive prostaglandin E2 144 .…”
Section: Efficacy and Mechanisms Of Mscs Therapy In Kdmentioning
confidence: 84%
“…Yu-Ting He 20 and others used hepatocytes/MSCs at a culture ratio of 5:1 for culture to generate stable primary hepatocytes. MINHUI LI 21 and others co-cultured hUc-MSC and HK-2 cells at a ratio of 12:1 to prove that hepatocyte growth factor derived from human umbilical cord blood mesenchymal stem cells promoted autophagy in HK-2 cells treated with AOPP. Studies have considered that the co-culture system can make BMSCs differentiate into hepatocytes to a certain extent 2125 , but the co-culture experiment of BMSCs such as Lange has proved that the proportion of BMSCs differentiation into hepatocytes is very small in a relatively short period of time 26 , the impact on the experiment is not large.…”
Section: Discussionmentioning
confidence: 99%